Pengaruh Pelaksanaan Senam Pada Lansia Terhadap Kualitas Tidur Di Panti Sosial Tresna Wredha Krikilan Glenmore Banyuwangi - Febrika Devi Nanda (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Elderly exercise is a sport that is easy to do, has low impact, and is suitable for the physique of the elderly. Gymnastics is highly recommended for those from the pre-elderly to the elderly because it has many benefits for the body. Sleep quality is a measure of how easy it is for a person to start sleeping and maintain sleep. The aim of this research was to determine the effect of elderly exercise on sleep quality at the Tresna Wredha Krikilan Glenmore Banyuwangi Social Services UPT. This type of research uses qualitative analytical research with a cross sectional approach with the chi square test. The sample from this research was the elderly who were at the Tresna Wredha Krikilan Glenmore Banyuwangi Social Services UPT, namely 55 respondents. Process data using SPSS. The results of this study show that the p-value is 816 which indicates that there is no relationship between elderly exercise and sleep quality at the UPT social service Tresna Wredha Krikilan Glenmore Banyuwangi. The conclusion of this study is that there is no relationship between elderly exercise and elderly sleep quality at the UPT social service Tresna Wredha Krikilan Glenmore Banyuwangi.